Development of Technology Adoption Framework on the use of Smart Classrooms - Sangalang , Nino (Gyan Management Journal, 2023)
Smart classrooms have emerged as an innovative solution for  educational institutions to deliver quality education during the  COVID-19 pandemic. The study focuses on students’ perspectives  and preferences regarding smart classrooms and recommends  effective implementation strategies based on educators’ experiences  and a well-established Technology Adoption Framework (TAF). The  study employed a mixed-methods approach, combining quantitative  and qualitative research methods. 188 students who experienced  learning in a smart classroom participated in the survey based on the  Technology Acceptance Model (TAM), and 16 experienced teachers  who taught in smart classrooms participated in qualitative research  based on SWOT and PESTLE analyses. Based on the researcher’s  analysis, it has been found that students are highly interested in  having a smart classroom in their educational institution. The study  highlights students’ receptiveness and sheds light on the valuable  insights shared by teachers regarding the optimum utilization of  smart technology in the classroom environment. The researcher has  developed a Technology Adoption Framework named SMARTCLASS,  which includes several crucial components such as communication,  training, management support, and user involvement. This framework  is expected to enhance the classroom’s overall teaching and learning  experience, ensuring optimal technology and resource utilization.
Keywords: Technology Adoption Framework (TAF); Technology Acceptance Model (TAM); SWOT analysis; PESTLE analysis